NEW WINE IN OLD WINE SKIN: AN EXPLORATION OF MAJOR CONSTRAINTS TO E-GOVERNMENT IMPLEMENTATION IN NIGERIA - Omeire, Edward; Omeire, Charles (European Scientific Journal, ESJ, 2014)
The past two decades has seen a growing zeal among African governments in embracing e-government. This is chiefly because egovernment has been peddled by development pundits as having the potential to stimulate economic growth, build institutional capacity, increase citizen participation and democratize political space. Many governments across Africa are now deploying ICTs to transform relationships between governments, their citizens and other stake holders. However, despite the opportunities e-government offers, they also introduce new challenges. These challenges are linked to some institutional and native contradictions within the African milieu. This paper explores major constraints surrounding implementation of e-government in Nigeria. The authors conclude that egovernment is beyond new technology. It includes cultural attitudes, human, environmental and political factors and these factors must be adequately dealt with before the full benefit of e-government will be maximized.